Social-Cognitive Predictors of Exclusive Breastfeeding among Primiparous Mothers in Addis Ababa, Ethiopia - Minas, Anteneh Girma; Ganga-Limando, Makombo (PLOS ONE, 2016)
Background Despite the presence of high impact interventions to improve infant and young child feeding, only about 52% of mothers in Ethiopia exclusively breastfeed their child for the first six months after delivery. Although the decision to breastfeed a child is ultimately that of the mother, this decision could be influenced by a variety of factors including social-cognitive ones. Objectives The objectives of the study were to describe the breastfeeding behaviour of primiparous mothers during their prenatal period in terms of intentions/goals, outcome expectancies, self-efficacy, and socio-structural factors and assess their exclusive breastfeeding (EBF) practices as well as identify the social-cognitive predictors of EBF practices among these mothers in Addis Ababa, Ethiopia. Methods A prospective follow up health facility-based study with quantitative methods was used with a sample of 233 primiparous women. Both structured and semi-structured questions were used for collection of data. The Statistical Package for Social Sciences (SPSS) version 21 was used for data analysis. Findings at the 95% confidence interval and P-value of 5% were reported as statistically significant. Results 39.1% (n = 59) of the respondents were found to have high breastfeeding self-efficacy, 51.4% (n = 71) have good breastfeeding outcome expectancies, and 6.5% (n = 9) respondents had supportive breastfeeding socio-structural factors. Bivariate correlation analysis showed positive and statistically significant correlation between each of breastfeeding self-efficacy, outcome expectancy, and socio-structural factors, with EBF practice. However, only breastfeeding self-efficacy and outcome expectancies were statistically significant predictors of EBF among the primiparous women when controlling for confounding variables. Conclusions and Recommendations Health programmes aimed at improving EBF among primiparous mothers should look beyond providing health information alone. Rather improving primiparous women’s breastfeeding self-efficacy and outcome expectancy is strongly recommended. Further community based large scale research is also recommended among similar groups of women.